2017
DOI: 10.1101/201970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell transcriptional profiling reveals cellular diversity, communication, and sexual dimorphism in the mouse heart

Abstract: INTRODUCTORY PARAGRAPHCharacterization of the cardiac cellulome—the network of cells that form the heart—is essential for understanding cardiac development and normal organ function, and for formulating precise therapeutic strategies to combat heart disease. Recent studies have challenged assumptions about both the cellular composition1 and functional significance of the cardiac non-myocyte cell pool, with unexpected roles identified for resident fibroblasts2 and immune cell populations3,4. In this study, we c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…and subsequent cardiac exsanguination. As previously described [10][11][12], the thoracic cavity was exposed and right atrium was cut to allow for cardiac perfusion through the left-ventricular apex (PBS, 0.9mM CaCl 2 , 200mM KCl), after which the heart was excised and ventricles were used for ow cytometry.…”
Section: Animal Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…and subsequent cardiac exsanguination. As previously described [10][11][12], the thoracic cavity was exposed and right atrium was cut to allow for cardiac perfusion through the left-ventricular apex (PBS, 0.9mM CaCl 2 , 200mM KCl), after which the heart was excised and ventricles were used for ow cytometry.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…Second, we only examined male mice in our study. Given that cardiac pathology is sex-speci c in mice [11,12] and in humans [16,45], cardiac cellular composition and gene expression are sexually-dimorphic [46]. Future work should examine the impact of biological sex in the development of diabetic cardiomyopathy.…”
Section: Study Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the heart, these include myocytes-which form the vast majority of the heart's volume-and non-myocytes, which outnumber myocytes. The application of single-cell flow cytometry and high throughput sequencing methodologies have transformed our understanding of cardiovascular tissue cellularity and, in particular, the heterogeneity of non-myocytes of the heart [1,2]. Single-cell transcriptomics enables joint examination of cellular heterogeneity and gene expression patterns, in addition to revealing shifts in these parameters in context of development or tissue stress.…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell transcriptomics enables joint examination of cellular heterogeneity and gene expression patterns, in addition to revealing shifts in these parameters in context of development or tissue stress. Recently, multiple single-cell transcriptomic studies have been published-in human and non-human contexts-that have examined the cellular landscape of the heart [2][3][4][5][6] and aorta [7,8]. Collectively, these studies have shown that cell types respond in an orchestrated manner to a range of physiological stressors, and that the cardiovascular tissues are ecosystems of interdependent cell types.…”
Section: Introductionmentioning
confidence: 99%